STUDI INTRUSI AIR LAUT DENGAN MENGGUNAKAN METODE RESISTIVITAS KONFIGURASI DIPOLEDIPOLE DI KAWASAN DESA LUBUK SABAN KECAMATAN PANTAI CERMIN PROVINSI SUMATERA UTARA - cristi nuara (Saintia Fisika, 2013)
The research detection of sea water intrusion had been performed using the electrical resistivity methods. The study was conducted in the village of Lubuk Saban, in the district of Pantai Cermin, North Sumatera Province. Taked of data using a resistivitimeter, Dipole-Dipole configuration. The obtained data are current (I) data and potential difference (V) data. Data processing is performed by using Res2dinv software, the result is in the form of 2D resistivity image of the subsurface resistivity. Rock resistivity values on the one track (a distance 25 m from the beach) ranged between 1,08 Ω .m – 116 Ω .m, the second track (a distance 34 m from the beach) ranged from 4,54 Ω m – 71,5 Ω m and the third track (a distance 44 m from the beach) ranged between 0,152 Ω m – 53,1 Ω m. Interpreted data showed that the intrusion of the sea water has been found in the village of Lubuk saban with the resistivity value of rocks ranged from 0,5 to 5 Ω m. Keywords: sea water intrusion, Dipole-Dipole configuration, porosity, permeability